Strategi Guru Pai Dalam Pengembangan Budaya Membaca Siswa Untuk Menambah Literasi Keagamaan di MAN 1 Pasaman - Anjelia Etri; Fauzan Fauzan; Jasmienti Jasmienti; Nurhasnah Nurhasnah (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2023)
This research is motivated by the low reading culture of students towards religious books. The school has made efforts to develop the reading culture of its students. This study aims to determine how the strategy of developing a culture of reading books at school by teachers of religious subjects such as al-Qur'an hadith, akidah akhlak and what are the inhibiting factors of student reading culture at MAN 1 Pasaman. Through this type of research that uses a qualitative approach that describes the strategy of developing a student reading culture in improving religious literacy at MAN 1 Pasaman. This study obtained data through interviews with Al-Qur'an Hadith teachers in class XI and Akidah Akhlak teachers in classes X and XI which are the main data, then interviews with several students and observations as supporting data from the interview results. The results of the study show that the reading culture development strategies pursued by the school and carried out by teachers are not fully satisfactory and still have shortcomings. There are 5 strategies for developing a student reading culture, namely: mandatory visits to the library, reading activities 15 minutes before learning, procurement of mading, procurement of literacy corners, procurement of competitions entitled literacy. all strategies have been implemented,but there are still shortcomings. The inhibiting factors for students' reading culture are the lack of reading habits and the lack of awareness of thr importance of reading textbooks, environmental factors, namely from peers and from the family environment and lastly, the lack of use of facilities and infrastructure at school.,